2023
DOI: 10.1055/a-2105-2177
|View full text |Cite
|
Sign up to set email alerts
|

A prospective multicenter study to evaluate the impact of cryotherapy on dysphagia and quality of life in patients with inoperable esophageal cancer

Toufic Kachaamy,
Neil Sharma,
Tilak Shah
et al.

Abstract: Background and Study Aims: Dysphagia palliation in inoperable esophageal cancer continues to be a challenge. Self-expanding metal stents have been the mainstay for endoscopic palliation but have a significant risk of adverse events (AE). Liquid nitrogen spray cryotherapy is an established modality that can be used with systemic therapy (ST). This study reports the outcomes of cryotherapy including dysphagia and quality of life (QoL) in patients on ST. Materials and Methods: A prospective multicenter cohort st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Preferred Reporting Items for Systematic Reviews and Meta-Analysis describing the details of the review process are shown in Figure 1. Four of the five included studies are available in full-text articles [14,15,17,18], while the one by Eluri et al is available as published abstract [16]. The characteristics of the included studies are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Preferred Reporting Items for Systematic Reviews and Meta-Analysis describing the details of the review process are shown in Figure 1. Four of the five included studies are available in full-text articles [14,15,17,18], while the one by Eluri et al is available as published abstract [16]. The characteristics of the included studies are given in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…1 . Four of the five included studies are available in full-text articles 14 15 17 18 , while the one by Eluri et al is available as published abstract 16 . The characteristics of the included studies are given in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations